FIBROADENOMA AND ITS CAUSES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article explores fibroadenoma, a common benign breast tumor, and its causes. It highlights the role of hormonal imbalance, genetic predisposition, and lifestyle factors in the development of fibroadenomas. The study also discusses diagnostic methods and treatment options.